A Tale of Two NGOs: Bangladesh’s Grameen Bank and BRAC - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
How has Bangladesh managed to outperform other low-income countries by doubling per capita GDP growth from 1.6% in the 1980s to 3.3% in the 1990s and beyond? The World Bank cites several key factors including an active civil society and strong partnerships forged by the government with NGOs. Two visionary NGO leaders, Nobel Peace Laureate, Muhammad Yunus (founder of Grameen Bank), and Fazle Hasan Abed (founder and chairman of BRAC), co-winner of the 2007 Clinton Global Citizen Award, visited Singapore in August and Sept 2007 to deliver two lectures on their respective organisations.